TINJAUAN LITERATUR TENTANG PENDEKATAN HOLISTIK PENDIDIKAN DASAR DI ERA DIGITAL DAN IMPLIKASINYA TERHADAP SELF-REGULATED LEARNING GENERASI ALPHA - Nurmeni Indratranovi; Sanseni Safitri; Suspita Nofa; Zelhendri Zel; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the relevance and implications of a holistic approach to elementary education in the digital era, with a particular focus on strengthening self-regulated learning (SRL) among Alpha Generation students. The urgency of this topic arises from the shifting learning characteristics of today’s elementary learners, who are highly immersed in digital technology, visually oriented, fast-paced, and require flexible and responsive learning environments. Using a systematic literature review method, this research analyzed 37 national and international articles published between 2015 and 2025. Data were collected from electronic databases such as Google Scholar, ERIC, DOAJ, and SINTA, followed by content analysis to identify patterns, themes, and key findings. The results show that holistic education integrated with digital learning contributes significantly to the development of cognitive, emotional, social, and spiritual competencies. Moreover, digital learning platforms provide opportunities for students to plan, monitor, and evaluate their learning processes independently, aligning with the core dimensions of SRL. The reviewed literature consistently indicates that the combination of holistic pedagogy and digital tools enhances students’ engagement, critical thinking, creativity, and autonomy. Findings from supporting data at SDN 25 Sungai Sirah Hilir further confirm that holistic-digital learning improves critical thinking skills with a moderate N-Gain score. Overall, this study highlights the importance of implementing holistic approaches in digital-based elementary education as a strategic effort to optimize SRL development for the Alpha Generation.